2000
DOI: 10.1073/pnas.210392097
|View full text |Cite
|
Sign up to set email alerts
|

Prostitution and the sex discrepancy in reported number of sexual partners

Abstract: One of the most reliable and perplexing findings from surveys of sexual behavior is that men report substantially more sexual partners than women do. We use data from national sex surveys and studies of prostitutes and their clients in the United States to examine sampling bias as an explanation for this disparity. We find that prostitute women are underrepresented in the national surveys. Once their undersampling and very high numbers of sexual partners are factored in, the discrepancy disappears. Prostitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 24 publications
(23 reference statements)
2
33
0
1
Order By: Relevance
“…Even allowing for age differences in the selection of partners by males and females, the most powerful factor appears to be female understatement (Baker & Bellis, 1995). Brewer et al (2000) showed that female prostitutes are usually underrepresented in the samples of such studies, and that the discrepancy is reduced when they are included, but it seems unlikely that the use of prostitutes explains the differences that we observed.…”
Section: Discussionmentioning
confidence: 63%
“…Even allowing for age differences in the selection of partners by males and females, the most powerful factor appears to be female understatement (Baker & Bellis, 1995). Brewer et al (2000) showed that female prostitutes are usually underrepresented in the samples of such studies, and that the discrepancy is reduced when they are included, but it seems unlikely that the use of prostitutes explains the differences that we observed.…”
Section: Discussionmentioning
confidence: 63%
“…Above all, the response rate of 35% is quite low and is lower than reported values for other European national sexual surveys. This low response rate naturally raises the concern that respondents may differ in some systematic way from those who refused participation; for example, women with extremely high numbers of partners may be underrepresented in national surveys (28). However, we note that the present analysis focuses on the speed at which new partners are obtained.…”
Section: Discussionmentioning
confidence: 91%
“…It appears that some women use their reproductive potential, that is, their sexuality, to initiate relationships with men who would not otherwise invest in them. Stated somewhat differently, men's preference for short-term mates and sexual variety (described later) creates a demand that some women use for financial or other material gains (Brewer et al, 2000). Many other women appear to engage in short-term sexual relationships when they perceive the potential for the development of a longer term relationship (Surbey & Conohan, 2000), suggesting that women sometimes use sexuality as a means to initiate a relationship with a potential marriage partner.…”
Section: Alternative Mating Strategiesmentioning
confidence: 99%
“…It is difficult to estimate the number of men who have resorted to prostitution as a means to secure short-term mates, because men are reluctant to admit to this behavior (Brewer et al, 2000). In a survey of 1,729 males between Prostitution.…”
Section: Short-term Mating Strategiesmentioning
confidence: 99%
See 1 more Smart Citation